2020
DOI: 10.1097/nnr.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Endurance of Hospitalized Older Adults With Chronic Obstructive Pulmonary Disease

Abstract: Background Chronic obstructive pulmonary disease (COPD) could lead to poor cardiopulmonary endurance, which affects quality of life and increases the risk of rehospitalization or mortality. However, studies investigating associated factors of cardiopulmonary endurance for COPD inpatients are scant. Objective The aim of the study was to investigate whether and how age, gender, COPD severity, body composition, dyspnea, respiratory muscle strength, and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Besides, we need a large number of subjects to verify our findings. Furthermore, fatigue is one of the most disabling symptoms of COPD [ 44 ], and COPD was reported to result in poor cardiopulmonary endurance [ 45 ], indicating fatigue level and cardiopulmonary should be taken into consideration in future analysis. The explanations of abbreviations in this study have been listed in Supplementary Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we need a large number of subjects to verify our findings. Furthermore, fatigue is one of the most disabling symptoms of COPD [ 44 ], and COPD was reported to result in poor cardiopulmonary endurance [ 45 ], indicating fatigue level and cardiopulmonary should be taken into consideration in future analysis. The explanations of abbreviations in this study have been listed in Supplementary Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, most of the studies evaluated the validity of the instruments, mainly by hypothesis testing [ 27 30 , 32 35 , 38 ], two studies evaluated reliability [ 36 , 39 ] and only two studied responsiveness [ 29 , 37 ]. Results of the measurement properties are presented in table S3 , while results related to COSMIN methodological quality of the studies and measurement properties are shown in table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Results of the measurement properties are presented in table S3 , while results related to COSMIN methodological quality of the studies and measurement properties are shown in table 2 . Some studies had a purpose other than assessing instrument validity [ 28 30 , 33 , 38 ]; however, our review team reached a consensus to include studies in which assessing the measurement properties of instruments was not the purpose of the study but still included data relevant to analyse measurement properties. Results of these analysis and the hypotheses formulated by the review team are presented in table S3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Cardiopulmonary endurance is an individual's ability to maintain long-term exercise or physical activity without tiring; it also refers to the heart's and lungs' ability to deliver oxygen to working muscles during continuous exercise. [9,10] Lower limbs explosive force is characterizing muscular work in a short time and grants the largest acceleration to the organism via fast muscular effort. [11][12][13] Anxiety represents the most common psychological disorder for young adults, it includes a series of negative disorders (phobia, panic, social anxiety, and so on).…”
Section: Introductionmentioning
confidence: 99%